استدراكات اصولیۃ في التفسير للآلوسي على الرازي: دراسة تحليلية نقدية (Al-Qamar, 2018)
Istidrāk mean correction of mistake, completion of deficiency and clarification of ambiguity. Islamic sciences have a long tradition of this area of research. The present article studies the juristic Istidrāks of Imām Shahāb al-Dīn al-Aʻlūsī (1270 AH/ 1854 AD) in his Tafsīr “Rūh al-Mʻānī fī Tafsīr al-Qur’ān al-ʻzīm wa al-Sabʻ al-Mathānī”on Imām Fakhr al-Dīn Al-Rāzī’s (544 AH/ 1149 AD) Tafsīr “Mafātīh al- Ghaib”. It concludes that these scholars have been objective while criticizing or differing with others. They very politely point out the mistakes of other scholars and try their best to guide their readers towards the accurate Islamic notions.
Keywords: Tafsīr; Istidrāk; jurisprudence; al-Aʻlūsī; Al-Rāzī